IMPACT OF PAST CORONAVIRUS INFECTION COVID 19 ON THE SEVERITY OF CORONARY HEART DISEASE - Mukhammadzhonov I.M; Tashtemirova I.M; Tukhtasinov A.A (Scholar Express Journals, 2024)
Coronary heart disease (CHD) is one of the leading causes of death in the world. The gold standard for the treatment of coronary artery disease in acute coronary vascular patency disorders is myocardial revascularization by stent placement, balloon angioplasty, or coronary artery bypass grafting. Achievements in the field of myocardial revascularization, the active introduction of drug-coated stents and effective antithrombotic therapy have led to the fact that coronary vascular restenosis has become a rare phenomenon in recent years
Keywords: Coronary; disease